PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA CV PRATAMA SHELLINDO JALAN KYAI TAPA NO.261, GROGOL, JAKARTA BARAT - Muhamad Ikhsan Aditya; Nefo Indra Nizar (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The research in this thesis aims to analyze the influence of Work Environment and Work Motivation on Employee Performance at CV Pratama Shellindo Jalan Kyai Tapa No.261, Grogol, West Jakarta. The method used in this study was a saturated sample with a population of 60 people, where all members of the population were made respondents. The data collection technique was carried out through observation and distribution of questionnaires. The data obtained were analyzed using validity tests, realism tests, classical assumption tests, simple linear regression analysis, multiple linear regression analysis, correlation coefficients, determination coefficients, and hypothesis tests (t-test and f-test). The results showed that the Work Environment had a significant influence on employee performance with a determination coefficient value of 98.3% and the hypothesis test was obtained from table > (3,699>1.67155). Work motivation has a significant influence with a determination coefficient value of 99.0% and the hypothesis test on the t-test is known that t calculates > table t, namely (76.421>1.67155). Simultaneously, these two variables affect employee performance (Fcal > Ftable) with an equation of regression values Y = 8.097 + 0.290 X1 + 0.527 X2 and a determination coefficient value of 99.2% indicating that 0.08% is influenced by other factors. This means that if there is an increase in the variables of Work Environment and Work Motivation, it will have the most dominant effect on employee performance, namely Work Motivation of 99.5%. The hypothesis test on the f-test is known that f is calculated > table f, namely (3565.332 > 3.16). Therefore, it can be concluded that Work Environment (X1) and Work Motivation (X2) simultaneously have a significant influence on employee performance.